2020 International SAUPEC/RobMech/PRASA Conference 2020
DOI: 10.1109/saupec/robmech/prasa48453.2020.9041105
|View full text |Cite
|
Sign up to set email alerts
|

Detecting inter-sectional accuracy differences in driver drowsiness detection algorithms

Abstract: Convolutional Neural Networks (CNNs) have been used successfully across a broad range of areas including data mining, object detection, and in business. The dominance of CNNs follows a breakthrough by Alex Krizhevsky which showed improvements by dramatically reducing the error rate obtained in a general image classification task from 26.2% to 15.4%. In road safety, CNNs have been applied widely to the detection of traffic signs, obstacle detection, and lane departure checking. In addition, CNNs have been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…However, their proposed methodology still requires that some training data be available for various population groups. A novel visualization technique which can be assistance to identify groups of people was proposed by research in [6] where potential discrimination could arise due to the usage of Principal Component Analysis (PCA). They used PCA to produce a grid of faces sorted by similarity and combining these with a model accuracy overlay.…”
Section: Background Studymentioning
confidence: 99%
See 2 more Smart Citations
“…However, their proposed methodology still requires that some training data be available for various population groups. A novel visualization technique which can be assistance to identify groups of people was proposed by research in [6] where potential discrimination could arise due to the usage of Principal Component Analysis (PCA). They used PCA to produce a grid of faces sorted by similarity and combining these with a model accuracy overlay.…”
Section: Background Studymentioning
confidence: 99%
“…Driver facial features based detection methods are based on facial features using various methods, i.e. CNN based Deep Learning Model [4],Generative Adversial Networks (GAN) [5],Principal Component Analysis [6], DriCare [7] where analysis was done on pupil, eyelids and head pose to detect drowsiness. This research proposes a robust method for vehicle driver drowsiness detection using facial features based head orientation and pupil detection where frame aggregation strategy is also used to ensure facial features processing under challenging circumstances, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For African contexts, this poses a challenge since the population is diverse and individuals can have many different facial attributes. Models trained using publicly available datasets do not generalise well in an African context [18].…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of datasets that fail to cover a wide range of ethnicities lead to bias in trained models when it comes to contexts with different nationalities. Prior work has shown that visualisation techniques can be used to identify bias in training datasets by identifying population groups where a classifier tends to fail [18]. This paper makes the following contributions in addressing population bias in driver drowsiness training datasets:…”
Section: Introductionmentioning
confidence: 99%